Pro Power BI Architecture Sharing, Security, and Deployment Options for Microsoft Power BI Solutions - Rad, Reza (Apress, 2018)
Architect and deploy a Power BI solution. This book will help you understand the many available options and choose the best combination for hosting, developing, sharing, and deploying a Power BI solution within your organization. Pro Power BI Architecture provides detailed examples and explains the different methods available for sharing and securing Power BI content so that only intended recipients can see it. Commonly encountered problems you will learn to handle include content unexpectedly changing while users are in the process of creating reports and building analysis, methods of sharing analyses that don't cover all the requirements of your business or organization, and inconsistent security models. The knowledge provided in this book will allow you to choose an architecture and deployment model that suits the needs of your organization, ensuring that you do not spend your time maintaining your solution but on using it for its intended purpose and gaining business value from mining and analyzing your organization's data. What You'll Learn: Architect and administer enterprise-level Power BI solutions Choose the right sharing method for your Power BI solution Create and manage environments for development, testing, and production Implement row level security in multiple ways to secure your data Save money by choosing the right licensing plan Select a suitable connection type-Live Connection, DirectQuery, or Scheduled Refresh-for your use case Set up a Power BI gateway to bridge between on-premises data sources and the Power BI cloud service.